Radiologische Diagnostik spinaler Tumoren: Teil 1: Allgemeine Tumordiagnostik und spezielle Diagnostik extraduraler Tumoren = Radiological diagnostics of spinal tumors : Part 1: general tumor diagnostics and special diagnostics of extradural tumors - Kloth, Jost; Wolf, Marcel; Rehnitz, Christoph; Lehner, Burkhard; Wiedenhöfer, Bernd; Weber, Marc-André (Der Orthopäde, 2012)
Radiological investigation of spinal tumors includes identification of the suspect lesions as well as their relation to surrounding critical structures, such as nerve roots and the myelon. With the use of computed tomography (CT) the delineation of bone and with magnetic resonance tomography the assessment of bone marrow and soft tissue are possible with high-spatial resolution and multi-planar reconstructions. The consolidation of clinical information, distribution pattern and morphology of the lesion itself results in the final radiological evaluation. Because of low invasiveness and complications, CT-guided biopsy is a common tool in cases of suspected lesions. With the help of multi-planar reconstructions even difficult approaches are possible without impairment of critical structures. This review article discusses typical imaging characteristics of common tumors originating from the vertebral column after a section on basic and general aspects of tumor diagnostics.